A novel class of evolutionarily conserved genes defined by piwi are essential for stem cell self-renewal. - Cox, D.N.; Chao, A.; Baker, J.; Chang, L.; Qiao, D.; Lin, H. (Genes & Development, 1998)
Germ-line stem cells (GSCs) serve as the source for gametogenesis in diverse organisms. We cloned and characterized the Drosophila piwi gene and showed that it is required for the asymmetric division of GSCs to produce and maintain a daughter GSC but is not essential for the further differentiation of the committed daughter cell. Genetic mosaic and RNA in situ analyses suggest that piwi expression in adjacent somatic cells regulates GSC division. piwi encodes a highly basic novel protein, well conserved during evolution. We isolated piwi homologs in Caenorhabditis elegans and humans and also identified Arabidopsis piwi-like genes known to be required for meristem cell maintenance. Decreasing C. elegans piwi expression reduces the proliferation of GSC-equivalent cells. Thus, piwi represents a novel class of genes required for GSC division in diverse organisms.